Glandular odontogenic cyst - Literature review and report of a paediatric case - Mohammad Faisal; Syed Ansar Ahmad; Uzma Ansari (Elsevier, 2015)
Glandular odontogenic cyst (GOC) is an extremely rare lesion occurring in the jawbones. The present paper is a review of 181 cases of GOCs reported in English literature, since it was first reported by Padayache and Van Wyk in 1987. Mandible was involved in 130 cases and maxilla in 51 cases. Anterior mandible was the most common area of involvement. Radiographic appearance was that of a unilocular radiolucency in 98 of 176 reported cases. Rest presented as multilocular radiolucency. Cortical expansion was observed in 136 of the 180 reported cases while cortex breach or perforation was seen in 81 cases. The treatment of choice was that of minor procedures that included enucleation with or without curettage, peripheral ostectomy, cryotherapy, etc. in 157 of the total 177 reported cases. Marginal jaw resection, segmental mandibulectomy etc. was reported in 20 cases. Although minor surgical procedures were the treatment of choice in most studies, two major studies of Kaplan et al. and Fowler et al. involving 111 and 46 cases, recorded a recurrence rate of 35.9 and 19.6%, respectively. The age range was between 11 and 82 years. The respective mean age of patients in the above mentioned studies was 45.7 for Kaplan's and 51 years for Fowler's whereas in our study, the mean age was 45.9 years. Very rarely does GOC presents itself in a paediatric patient. The paper also reports a case of an 11-year-old child whose histopathogy came out to be a case of a GOC.